2013
DOI: 10.1136/annrheumdis-2013-204244
|View full text |Cite|
|
Sign up to set email alerts
|

Articular chondrocyte network mediated by gap junctions: role in metabolic cartilage homeostasis

Abstract: Objective This study investigated whether chondrocytes within the cartilage matrix have the capacity to communicate through intercellular connections mediated by voltage-gated gap junction (GJ) channels. Methods Frozen cartilage samples were used for immunofluorescence and immunohistochemistry assays. Samples were embedded in cacodylate buffer before dehydration for scanning electron microscopy. Co-immunoprecipitation experiments and mass spectrometry (MS) were performed to identify proteins that interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 47 publications
3
82
0
1
Order By: Relevance
“…13,14 While the first two molecules disappear in the course of chondrogenesis, 13 gap junctions can still be found in mature cartilage. 15 Gap junctions are intercellular channels formed by connexins that allow for rapid exchange of ions, metabolites, and other small-molecule messengers. 16 They are expressed in virtually all tissues and are involved in various cellular functions, including cell growth, differentiation, and death.…”
mentioning
confidence: 99%
“…13,14 While the first two molecules disappear in the course of chondrogenesis, 13 gap junctions can still be found in mature cartilage. 15 Gap junctions are intercellular channels formed by connexins that allow for rapid exchange of ions, metabolites, and other small-molecule messengers. 16 They are expressed in virtually all tissues and are involved in various cellular functions, including cell growth, differentiation, and death.…”
mentioning
confidence: 99%
“…In addition, caldesmon plays important roles in the migration of nonmuscle cells via regulating the actin-myosin system (82), and caldesmon binding to myosin has been reported to result in the enhancement of axon extension (83). Interestingly, we have found that chondrocytes from OA patients contain longer cellular extensions (more than 200 m in length) when compared with chondrocytes in healthy cartilage (7). Further studies will be necessary to reveal the role of Cx43 in these processes and to discern its function in OA chondrocytes.…”
Section: Fig 2 Cx43-nuclear and Perinuclear Interactorsmentioning
confidence: 72%
“…In fact, the eye lens and articular cartilage of adults are avascular organs, and because no blood supply reaches these tissues, it has been reported that cells in these tissues are maintained by the movement of fluids, ions, nutrients (e.g. glucose), and metabolites through a network of GJs (7,54,55). In addition, results from different reports strongly suggest that inhibition of GJIC modifies glucose uptake and that glucose levels modify Cx43 gene expression (56).…”
Section: Fig 2 Cx43-nuclear and Perinuclear Interactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct cell-to-cell communication has been shown in the superficial zone of articular chondrocytes [155]. A paradigm challenging study has even shown that chondrocytes in situ may form long cell processes, 5 to 150 microns in length, that permit communication through gap junction channels [156]. Increased presence of gap junction plaques and Cx43 expression have been found in synovial lining cells obtained from the knee of patients with osteoarthritis [157].…”
Section: Connexins In Cartilage Ligaments and Tendonsmentioning
confidence: 99%